2010
DOI: 10.1007/s00404-010-1361-0
|View full text |Cite
|
Sign up to set email alerts
|

Failure of prostaglandin induction labor in a Müllerian abnormality

Abstract: Rudimentary-horn pregnancy (RHP) is a rare condition which is usually presented as a rupture of the pregnant horn during the second or third trimester, resulting in life-threatening bleeding. The authors report two cases of RHP which were diagnosed at the time of labor induction following fetal death diagnosis. Although the failure of prostaglandin induction to initiate labor could suggest that an additional obstructive Müllerian uterine anomaly is present, a directed investigation of such anomaly is more acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…An important clinical clue to diagnosis again was failure of prostaglandin induction with no cervical changes. This point is also reported by Abreu  et al 8 in their case report on two patients who were diagnosed at the time of labour induction following fetal demise. Samuels and Awonuga9 reported a young primigravida with a history of an US diagnosis of bicornuate uterus who presented with mild abdominal pain.…”
Section: Discussionsupporting
confidence: 80%
“…An important clinical clue to diagnosis again was failure of prostaglandin induction with no cervical changes. This point is also reported by Abreu  et al 8 in their case report on two patients who were diagnosed at the time of labour induction following fetal demise. Samuels and Awonuga9 reported a young primigravida with a history of an US diagnosis of bicornuate uterus who presented with mild abdominal pain.…”
Section: Discussionsupporting
confidence: 80%
“…The top 10 research priorities for female and unexplained infertility were identified during a consensus development meeting involving 41 participants from 11 countries (Table 1). 1 Anjila Roumia, MD, 1 Samantha Yee, Ph.D, 2 Ari Y. Baratz, MD, 3 Karen B. Glass, MD, 2 Prati Sharma, MD, 2 Clifford Lawrence Librach, MD 2 1 CReATe fertility centre, Toronto, ON, Canada; 2 CReATe Fertility Centre, Toronto, ON, Canada; 3 University of Toronto, Toronto, ON, Canada.…”
Section: E222mentioning
confidence: 99%